The sacred depths of nature - Goodenough, Ursula (ISSR Library., 1998)
For many of us, the great scientific discoveries of the modern age - the Big Bang, evolution, quantum physics, relativity - point to an existence that is bleak, devoid of meaning, pointless. But in The Sacred Depths of Nature, eminent biologist Ursula Goodenough shows us that the scientific world view need not be a source of despair. Indeed, it can be a wellspring of solace and hope. This eloquent volume reconciles the modern scientific understanding of reality with our timeless spiritual yearnings for reverence and continuity. Looking at topics such as evolution, emotions, sexuality, and death, Goodenough writes with rich, uncluttered detail about the workings of nature in general and of living creatures in particular. Her luminous clarity makes it possible for even non scientists to appreciate that the origins of life and the universe are no less meaningful because of our increasingly scientific understanding of them. At the end of each chapter, Goodenough's spiritual reflections respond to the complexity of nature with vibrant emotional intensity and a sense of reverent wonder.; A beautifully written celebration of molecular biology with meditations on the spiritual and religious meaning that can be found at the heart of science, this volume makes an important contribution to the ongoing dialogue between science and religion. This book will engage anyone who was ever mesmerized-or terrified-by the mysteries of existence.